Validity, reliability, and invariance across sex of a German version of the Behavioral Regulation in Exercise Questionnaire - Cocca, A.; Kopp, M.; Greier, K.; Labek, K.; Ruedl, G. (Frontiers in Psychology, 2024)
Objective: Since there is no scientifically validated German version of the Behavioral Regulation in Exercise Questionnaire (BREQ-3), the aim of this study was to assess its psychometric parameters and invariance across sex in a sample of German-speaking young adults. The BREQ-3 is an instrument measuring the social and internal influences of motivation toward exercising. This tool is widespread within the scientific community and has been validated in several languages.